A urbanização do Amazonas no presente: a manutenção da primazia urbana de Manaus / The urbanization of Amazonas in the present: maintenance of the urban primacy of Manaus - Sousa, Norma Maria Bentes de (Revista de Direito da Cidade, 2022)
Resumo A inserção subordinada do Estado do Amazonas na divisão regional do trabalho, via especialização monoprodutiva configurada no empreendimento Zona Franca de Manaus (ZFM), foi ditada pelos centros dominantes, localizados nas escalas nacional/global. O objetivo deste artigo é entender o processo de urbanização no estado do Amazonas no contexto da industrialização incentivada pelo Estado, via modelo ZFM. A pesquisa utilizou dados secundários, dos censos demográficos e das pesquisas econômicas do IBGE, referentes ao período da urbanização com industrialização (1967– 2014). A análise identificou fatores responsáveis pela concentração da urbanização (e da riqueza) sob a dominância da ZFM: baixa articulação da principal atividade econômica — a industrial, localizada em Manaus, — com as demais frações do território amazonense; crescente migração da população dos municípios do Amazonas para a capital estadual; e manutenção da rede urbana dendrítica. A produção industrial transplantada, centrada nas etapas produtivas finais e pouco articulada com a produção regional, promoveu ao longo do tempo o esvaziamento demográfico-econômico dos demais municípios amazonenses e reforçou uma urbanização “voltada para trás”, a da primazia urbana de Manaus. Nesse processo, a capital amazonense constituiu-se no espaço mais urbanizado da Amazônia, consolidando-se como metrópole regional e demonstrando, em última instância, que o comando e as decisões sobre o desenvolvimento socioeconômico do Amazonas continuam sendo externos a esse espaço sub-regional. Palavras-chave: Urbanização. Estado do Amazonas. Manaus. Zona Franca de Manaus. Industrialização. Abstract The subordinate integration of the Amazonas State (Brazil) in the regional division of labor, which took place via monoproductive specialization as embodied by the Manaus Free Trade Zone (MFTZ) enterprise, was dictated by the dominant centers on the national/global scale. This paper aims to understand the process of urbanization in the Amazonas State in the context of the industrialization encouraged by the State, via the MFTZ model. The study makes use of secondary data from demographic censuses and IBGE economic surveys concerning the urbanization–industrialization period (1967–2014). The analysis identifies factors responsible for the urbanization (and wealth) concentration within the sphere of MTFZ dominance: the weak integration of the main economic activity — the industrial activity in Manaus — with the remainder of the Amazonas State; increasing migration to the state capital Manaus from other municipalities of the Amazonas State; and maintenance of the dendritic urban network. The transplanted industrial activities, focused on the final production stages and poorly integrated with the regional production, have over time promoted a demographic and economic draining of non-capital Amazonas municipalities and reinforced a “backward-oriented” urbanization process in Manaus, reflecting its urban primacy. In this way, the state capital of Amazonas became the most urbanized space in the Amazon region, consolidating itself as a regional metropolis, and ultimately showing that the command and the decisions on the socioeconomic development of the Amazonas State remain external to that sub-regional space. Keywords: Urbanization. Amazonas State (Brazil). Manaus. Manaus Free Trade Zone. Industrialization.